HUBUNGAN ANTARA PERBANDINGAN SOSIAL DAN KETANGGUHAN MENTAL PADA PEMAIN BASKET REMAJA DI JAKARTA - Darrell Khoo; Monty P. Satiadarma; Linda Wati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In competitive basketball, adolescent players operate in environments demanding high performance and mental strength to face competition and social evaluation. This study aims to examine the relationship between social comparison and mental toughness among adolescent basketball players in Jakarta. Participants were 110 adolescent basketball players aged 12-18 in Jakarta, with data collected via online self-report questionnaires. Social Comparison was measured using the Iowa-Netherlands Comparison Orientation Measure (INCOM) adapted to basketball, and mental toughness was measured using the Sport Mental Toughness Questionnaire (SMTQ). Results showed a significant positive relationship between social comparison and mental toughness (r = 0.438; p < 0.001), indicating that a higher tendency to compare oneself relates to higher mental toughness. Mental toughness and social comparison also varied significantly based on gender, playing position, training duration, independent training, and achievement.